A Scoping Review of Eosinophilic Pneumonia and Antidepressants: An Association Not to Be Overlooked - Jaron Steiner; Leonie Steuernagel; Fotios Drakopanagiotakis; Konstantinos Bonelis; Paschalis Steiropoulos (Diseases)
Background: Eosinophilic pneumonias denote a rare condition, wherein infiltrating eosinophilic granulocytes accumulate within the lung parenchyma. Although eosinophilic pneumonias may be idiopathic, they are also associated with secondary causes. More than 110 medications have been linked to eosinophilic pneumonia, including several antidepressants. This review presents an analysis of case reports of eosinophilic pneumonia correlated to antidepressants. Objectives: The objectives of this study are to provide a contemporary overview of the literature delineating eosinophilic pneumonia as a potential sequela of antidepressant medication treatment, and to discuss possible pathogenetic mechanisms linking antidepressants to eosinophilic pneumonia. Methods and Data Selection: A literature search was performed in PubMed and Scopus databases from 1963 to October 2024. The search strategy used the terms “eosinophilic pneumonia AND antidepressants”. Sources included in this review were screened for relevance, focusing on references discussing eosinophilic pneumonia associated with any class of antidepressants. Case reports meeting the diagnostic criteria for acute eosinophilic pneumonia (AEP) or chronic eosinophilic pneumonia (CEP) were included in the review. Clinical, epidemiological, laboratory, radiology and bronchoscopy data, implicated antidepressant and dosage, and therapeutic interventions were reported. Results: This study found that various types of antidepressants are associated with AEP and CEP. The clinical presentation ranges from mild symptoms to respiratory failure and intubation. Outcomes were favorable in most cases, with complete remission achieved after discontinuation of the causative drug and, in severe cases, a short course of corticosteroids. Conclusions: Although a rare cause, antidepressants may lead to eosinophilic pneumonia, and should be considered in the differential diagnosis of unexplained pulmonary infiltrates. Clinical suspicion must be aroused, as early recognition would prevent unnecessary work-up and navigation of the diagnosis.